Surgical treatment of anomalous aortic origin of the coronary artery in paediatric patients: a Chinese single-center experience - Kai Luo; Bin Ji; Qi-Liang Zhang; Xiao-Yang Zhang; Yan-Jun Pan; Zhong-Qun Zhu; Qiang Chen; Xiao-Min He; Jing-Hao Zheng (BMC Surgery)
Abstract Purpose An anomalous aortic origin of the coronary artery (AAOCA) is a rare congenital heart disease. Some high-risk anatomical structures are at risk of inducing cardiogenic shock or even sudden death. This article summarizes our surgical experience with AAOCA in paediatric patients. Methods We retrospectively analysed the clinical data of 27 paediatric AAOCA patients admitted to the Department of Cardiothoracic Surgery in our hospital from July 2015 to June 2023 and summarized the surgical treatment experience and follow-up results. Results A total of 27 patients were included in this study, including 14 patients with an anomalous left coronary artery (ALCA) and 13 patients with an anomalous right coronary artery (ARCA). A comparison of clinical data between ALCA and ARCA patients revealed that the preoperative left ventricular ejection fraction (LVEF) in ALCA patients was significantly lower than that in ARCA patients (p < 0.05). There were significantly more patients with preoperative complications, such as major adverse cardiovascular events (MACEs) and mitral regurgitation (MR), in the ALCA group than in the ARCA group (p < 0.05). No postoperative adverse events such as severe bleeding, mediastinitis, central nervous system complications, the need for reoperation, pacemaker implantation, pleural effusion complications occurred after operation.The duration of follow-up was 58.5 (31.5, 77.3) months. During the follow-up period, none of the patients presented symptoms such as chest tightness or chest pain, and cardiac CTA revealed unobstructed coronary arteries. Compared with the preoperative LVEF, the LVEF significantly improved at the last follow-up (p < 0.05). Conclusions Patients with an AAOCA should be taken seriously, and surgical treatment should be considered for these patients. Surgery should be considered for patients with ALCA as well as patients with ARCA with symptoms of myocardial ischaemia or a positive diagnosis of myocardial ischaemia or ventricular arrhythmia. For patients with other congenital heart defects that require surgical treatment, if the AAOCA is a high-risk anatomical structure, simultaneous surgery should be considered. The surgical method should be tailored to the coronary artery anatomy of the individual patient.